Monitoring urban wetlands restoration in Qinghai Plateau: Integrated performance from ecological characters, ecological processes to ecosystem services. (June 2019) - Mao, Xufeng; Wei, Xiaoyan; Jin, Xin; Tao, Yaqin; Zhang, Zhifa; Wang, Wenyin
Highlights: A framework was developed for plateau urban wetland restoration assessment in China. The framework includes multiple indicators from ecological characters, ecological processes to ecosystem services. The case assessment approach is general and can be used to inform other restoration assessment studies. Abstract: The assessment for wetland restoration effect is crucial for wetland management and sustainable utilization. This issue is evaluated in this study and applied to four wetlands in the Xining city, China. A framework was developed in the present work to evaluate the wetland restoration and detect holistic characters in terms of ecological characters, ecological processes and ecosystem services. Supporting data was collected by monthly monitoring through a combination of laboratory analysis, fielding survey and questionnaire survey. A matrix linking all indicators was constructed and the inter-relationship among the above factors was analyzed using the SPSS statistical software. The research results revealed that: (1) With respect to selected monitoring indices, four wetlands exhibited a significant difference (p < 0.01) at the two time points (2014 and 2018). The comprehensive restoration scores (CRS) of four wetlands were 51.1, 70.3, 59.0 and 56.1 for WS1, WS2, WS3, WS4, respectively, which ranged from Considerable to Good Restoration; (2) Ecosystem services gave the highest scores and scoring ratio (average of 38.9, accounting for 66.2% of total scores), followed by ecological processes (average of 14.2, accounting for 23.6% of total scores), and finally the ecological characteristics (average of 5.9, accounting for 10.1% of total scores); (3) About 74% tested assessment indicators exhibited significant inter-relations (P < 0.05), among which 68% indicators presented positive inter-relation. The currently studied wetlands present a mutual-reinforcement restoration mode that is similar to a synergistic effect. This research highlights the importance of comprehensive assessment of wetland restoration on the perspective of both external characteristics and internal processes and social responses.